HDAC6-specific inhibitor alleviates hashimoto's thyroiditis through inhibition of Th17 cell differentiation. (September 2022) - Chang, Qungang; Yin, Detao; Li, Hongqiang; Du, Xin; Wang, Zipeng; Liu, Yihao; Zhang, Jieming
Abstract: Objective: Hashimoto's thyroiditis (HT) is one of the commonest autoimmune disorders. This study was performed to investigate the potential effect of histone deacetylase 6-specific inhibitor (HDAC6i) on Th17 cell differentiation in animal model and the underlying mechanism. Methods: Experimental autoimmune thyroiditis (EAT) mouse model was established by subcutaneously immunization of porcine thyroglobulin (pTg) and adjuvant, and the HDACi Tubastatin A (TSA) or HDAC6i (ACY-1215) was intraperitoneally injected into mice in the following. The histological examination and immune analysis in EAT mice were carried out. Next, the CD4+ T cells were isolated from peripheral blood mononuclear cells (PBMCs) of EAT mice followed by Th17 cell differentiation assay. The associated factor levels, and the protein interaction between HDAC6 and PKM2 were examined. Subsequently, the effect of STAT3 activation on Th17 cell differentiation was explored. Results: ACY-1215 or TSA treatment reduced lymphocytic infiltration and alleviated thyroid tissue injury in EAT mice. Correspondingly, either ACY-1215 or TSA treatment reduced the levels of anti-thyroglobulin (Tg), anti-thyroid peroxidase (TPO), IL-17A, and IFN-γ in the serum, decreased Th17 cell differentiation, but enhanced TGF-β level and promoted Treg cell differentiation. In vitro, after induction of Th17 cell differentiation from CD4+ T cells, HDAC6 activity and Th17 cell differentiation were significantly decreased when treated with ACY-1215 or TSA. HDAC6 could interact with PKM2, and HDAC6 overexpression promoted the phosphorylation of STAT3 and PKM2 nuclear translocation. Furthermore, the STAT3 activator treatment reversed the effects of ACY-1215 or TSA treatment. Conclusion: HDAC6i suppresses Th17 cell differentiation and attenuates HT via PKM2/STAT3 axis. Highlights: HDAC6-specific inhibitor alleviated pathological injury of HI. HDAC6 mediates the deacetylation of PKM2 and its nuclear translocation. HDAC6-specific inhibitor reduced differentiation of Th17 cells via regulating PKM2/STAT3 axis.